Comparative effects of eggplant (Solanum melongena) and water spinach (Ipomoea aquatica) crude extract ointments on second degree thermal burns of male albino rats. - Sanchez, Gemjho G. (2012)
This study entitled Comparative effects of Eggplant (Solanum melongena) and Water Spinach (Ipomoea Aquatica) Crude Extract Ointments on Second Degree Thermal Burns of Male Albino rats was conducted to determine the healing effects of eggplant fruit and water spinach leaves crude extract ointment on the second-degree burns of albino rats. A total of thirty-six rats were acclimatized for 14 days. Their fur was shaved and a seconddegree burn was induced by the heating of the head of a metal hammer, at the upper lateral part of the right thigh of the albino rat’s skin for three seconds only. The collected plants were chopped and mashed, then soaked in 95% ethanol for three days and filtered in a cheesecloth. Production of the ointments was done by the initial process of a rotary evaporator and the heating and addition of paraffin wax. The ointments were applied topically to the induced second-degree burns of the albino rats. They were treated with the crude extract ointment once a day. The healing process of the second-degree burn was noted daily by observing the three parameters of burning which are: absence of reddening, scab removal, and reappearance of fur. Results showed that there is a significant difference in the healing rate of induced second-degree burns between eggplant and water spinach crude extract ointments. It indicated that the eggplant crude extract ointment can heal burns faster than that of water spinach crude extract ointment, but the commercial used drug is still more advantageous than that of the two tested treatments.